Petrography and mineralogy of the white marble and black stone of Göktepe (Muğla, Turkey) used in antiquity: New data for provenance determination. (June 2018) - Brilli, M.; Lapuente Mercadal, M.P.; Giustini, F.; Royo Plumed, H.
Abstract: The discovery near Göktepe (Muğla province, Western Turkey) of an ancient quarrying site of white marbles and black stones has recently been reported by some authors. Assigning the provenance of stone from ancient artifacts to Göktepe is currently possible mainly thanks to chemical, EPR and MGS data. Petrographic description, which many researchers use to characterize ancient marbles, is still incomplete. Several thin sections of both types of stone were thus examined in this study, and also used for cathodoluminescence analysis. As the rock is >99% calcite, trace minerals could only be detected in some samples by XRD analysis of insoluble residues after acetic acid attack. Data on strontium and manganese contents and carbon and oxygen isotopes were also recorded, for better understanding of some petrographic features. A new method of grain size characterization was tentatively introduced to improve the description of grain size variability in the white marble. Microstructure and grain size measurements on thin sections of this marble identify two petrographic varieties: the first is extremely fine with signs of dynamic recrystallization, and the second exhibits texture and MGS similar to those of Carrara marble. Statuary samples of white marble from Villa Adriana (Tivoli, Rome), preliminarily assigned in a previous study partly to Carrara and partly to Göktepe quarry, are reconsidered here. A certain degree of variability was found in the structures and textures in the thin sections of the Göktepe black stone. It may have undergone transformations at an advanced stage of diagenesis. One important source of this variability seems to be a fluid alteration event, revealed by both isotopic and chemical data and trace mineral assemblages. Highlights: Archeometric characterization of the stones of the Göktepe ancient quarries Petrography and mineralogy variability is described for recognition of these marbles in unknown marble artefacts Grain size distribution and Most Frequent Size (MFS) are introduced in characterization studies of ancient white marbles New petrographic classification for the Göktepe black stone is proposed